Apremilast Use for Moderate-to-Severe Atopic Dermatitis in Pediatric Patients - Rachael C. Saporito; David J. Cohen (Karger Publishers, 2016)
Atopic dermatitis (AD) is a chronic, pruritic skin disease often complicated by bacterial superinfection affecting 10.7% of American children. The pathogenesis involves a skin barrier breakdown in addition to dysfunctional innate and adaptive immune response, including an unbalanced increase in T-helper 2 cells and hyperimmunoglobulinemia E. The increased numbers of T-helper 2 cells are involved in stimulating the production of immunoglobulin E and eosinophilia by releasing interleukin-4, -5, and -13 as well as in decreasing protection against bacterial superinfection by releasing interleukin-10. The current Food and Drug Administration-approved symptomatic treatment for AD includes topical ointments, topical and systemic corticosteroids, topical immunomodulant therapy, antibiotics, and phototherapy, but there are not approved targeted therapies or cures. By presenting a case of an 8-year-old African-American boy, this case report supports novel therapy of moderate-to-severe AD with apremilast, a phosphodiesterase type 4 inhibitor. Apremilast has recently completed the phase 2 clinical trial (NCT02087943) for treatment of AD in adults. This case report illustrates the potential for apremilast as a treatment for AD in children, where there is a great need for safe and effective medications.